In Vitro Antimicrobial Activity Evaluation of Ginger (Zingiber officinale) Absolute Ethanol Extract against Uropathogenic Escherichia coli (UPEC) - Angeline Felicia; Kartuti Debora; Ramadhani Ramadhani (Faculty of Medicine Universitas Airlangga, 2022)
Highlights: 1. Ginger (Zingiber officinale) has an antimicrobial activity against Uropathogenic Escherichia coli (UPEC) which commonly causes urinary tract infection (UTI) in women.2. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of ginger against UPEC in this study was 1000 mg/ml. AbstractIntroduction: Uropathogenic Escherichia coli (UPEC) is commonly found in the urine culture of women with urinary tract infections (UTIs) and is often resistant to several antimicrobials. Herbals, such as ginger (Zingiber officinale), are known to have antimicrobial activity against various microorganisms. This study was conducted to determine the antimicrobial activity of ginger against UPEC.Methods: This was a true experimental study to determine the minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) using agar dilution method. The McFarland 0.5 suspension of UPEC was inoculated on agar with 6 different ginger concentrations, i.e. 2,000 mg/ml, 1,000 mg/ml, 500 mg/ml, 250 mg/ml, 125 mg/ml, and 62.5 mg/ml. The MIC and MBC were read as the lowest concentration without visible growth.Results: No visible growth of bacteria on agar at a concentration of 2,000 mg/ml and 1,000 mg/ml. Thus, the value of MIC and MBC for UPEC was 1,000 mg/ml.Conclusion: Ethanol extract of ginger has antimicrobial activity against UPEC. In this study, the MIC and MBC for UPEC was 1,000 mg/ml.